Introducing research methodology : a beginner's guide to doing a research project - Flick, Uwe, 1956- (Thousand Oaks, Calif. : Sage Publications, 2011)
'Introducing Research Methodology' gives readers the fundamental data collection and analysis skills that they need for their first project, as well as a good understanding of the research process as a whole.
PART ONE: ORIENTATION -- Why Social Research? -- From Research Idea to Research Question -- Reading and Reviewing the Literature -- PART TWO: PLANNING AND DESIGN -- Planning Social Research: Steps of the Research Process -- Designing Social Research -- Deciding Your Methods -- PART THREE: WORKING WITH DATA -- Gathering Data: Quantitative and Qualitative Approaches -- Analyzing Quantitative and Qualitative Data -- E-Research: Doing Social Research Online -- Integrated Social Research: Combination of Different Approaches -- PART FOUR: REFLECTION AND WRITING -- What Is Good Research? Evaluating Your Research Project -- Ethical Issues in Social Research -- Writing Research and Using Results
Includes bibliographical references (p. [256]-263) and index.
Keywords: Social sciences -- Research; Research -- Methodology